SUITABILITY ANALYSIS OF YASIN BOOK WITH INDONESIAN STANDARD MANUSCRIPTS (MSI) - Mohd Amin Abbas; Najib Irsyadi (Nida Al-Qur'an: Jurnal Pengkajian Islam, 2025)
The rapid publication of Al-Qur’an mushafs in Indonesia requires the application of consistent standards to maintain the sanctity of the recitation. The Lajnah Pentashihan Mushaf al-Qur’an (LPMQ) was established to ensure that every published mushaf adheres to the agreed-upon guidelines to preserve the integrity of Al-Qur’an recitation. This study aims to ensure that the Yasin books used in religious activities in Indonesia comply with the Mushaf Standar Indonesia (MSI), with the goal of preventing recitation errors that could affect the understanding and sanctity of the Al-Qur’an. The approach used in this study is library research with a qualitative descriptive method, relying on written sources such as books, manuscripts, and relevant articles. This research also collects primary data in the form of books discussing MSI and secondary data from various relevant scholarly journals. All collected data were analyzed using the interactive analysis model of Huberman and Miles. The book studied is "Surat Yasin, Tahlil, dan Istighasah," published by Afif Media Surabaya. The results of this study show several discrepancies in the book’s writing, particularly related to the use of Hamzah wasl, placement of waqaf marks, and application of mad thabi'i. However, these discrepancies are primarily due to differences in the application of printing guidelines across various editions of the Al-Qur’an, especially earlier printings that tend to adopt Middle Eastern writing styles